2020
DOI: 10.1002/rrq.323
|View full text |Cite
|
Sign up to set email alerts
|

English Learners’ Acquisition of Academic Vocabulary: Instruction Matters, but So Do Word Characteristics

Abstract: In this cluster randomized control trial study, the authors explored the efficacy of an intervention designed to improve second‐grade English learners’ knowledge of challenging, high‐utility English vocabulary. The authors also examined whether the intervention had a differential effect on content words that differ on two attributes (cognate status and abstractness designation) and whether the effects lasted across time. Within schools, teachers were randomly assigned to treatment or control conditions, result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 62 publications
(121 reference statements)
0
8
1
Order By: Relevance
“…Li & Hafner, 2022). Furthermore, Formal English vocabulary is usually used in academic English writing which is characterized by fewer personal pronouns and no slang or colloquial phrases (August et al, 2021;Wei, 2021). It also has more sophisticated sentence patterns.…”
Section: Literature Review Formal English Vocabulary Knowledgementioning
confidence: 99%
See 2 more Smart Citations
“…Li & Hafner, 2022). Furthermore, Formal English vocabulary is usually used in academic English writing which is characterized by fewer personal pronouns and no slang or colloquial phrases (August et al, 2021;Wei, 2021). It also has more sophisticated sentence patterns.…”
Section: Literature Review Formal English Vocabulary Knowledgementioning
confidence: 99%
“…Having a large repertoire of vocabulary, especially formal vocabularies or words may support the EFL learners in listening, reading, and speaking skills. Furthermore, researchers (August et al, 2021;Wei, 2021) assert that having a command of EFVK can improve the quality of the learners' writing and ease of understanding messages connotationally or denotationally conveyed within texts. Although the accuracy of choosing a formal vocabulary is not the only thing to make writing considered to be credible and make it easier to understand the content of the writing (Lestari et al, 2022).…”
Section: Literature Review Formal English Vocabulary Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Some interventions have used explicit bridging techniques to promote cognate awareness (Baker et al., 2014; Carlo et al., 2004; Gersten et al., 2007; Graves et al., 2012; Kieffer et al., 2009). For example, students can receive explicit instruction about cognates and false cognates, work with peers to find cognates in their texts, and then analyze the cognates for similarities and differences across languages (e.g., August et al., 2018; August et al., 2021).…”
Section: Cross‐cutting Practices To Enhance Language and Scaffold Ins...mentioning
confidence: 99%
“…Taking a higher–level view of this body of research, a recent meta–analysis of 43 empirical studies conducted by Silverman et al (2020) found that multicomponent interventions focused on language produced moderate positive effects for both EM students and non–EM students, but the effects were more strongly positive for EM students. Specifically, interventions that incorporated a focus on syntax were found to impact reading comprehension (e.g., by supporting students’ access to sentence–level meaning–making skills, interventions helped them make meaning of texts; see also August et al, 2021), whereas interventions that incorporated vocabulary and morphology as key foci were found to affect vocabulary outcomes (e.g., by giving students tools to understand and apply the meanings of words).…”
Section: Enhancing Instruction and Intervention With Languagementioning
confidence: 99%